TEACHERS' BELIEFS AND CONSTRAINTS IN ADOPTING LEARNER-CENTERED PEDAGOGY; AN ANALYSIS OF TEACHER-CENTERED METHODS IN TANZANIAN TEACHER TRAINING COLLEGES - Mustapha Almasi; Susan Mwangu Rumulika; Johari Hakimu; Justine N Mbukwa (PEDAGOGIK : JURNAL PENDIDIKAN, 2024)
Modern teaching prioritizes student-centered learning, yet teacher-centered methods (TCM) still exist in many contexts, including Tanzanian colleges. This study investigates the factors that motivate the continued use of TCM in selected teacher training institutions in Tanzania. Using a quantitative approach, data were collected from 150 college teachers through structured questionnaires, analyzed with the Relative Importance Index (RII) to rank the motivational factors. The research findings reveal three main factors driving the use of TCM, which consist of teachers' belief in its effectiveness, poor student cooperation perception, and low student learning ability. Additional but less significant factors include class size, resource limitations, and standardized testing demands. This study concludes that deeply rooted teacher beliefs and contextual classroom challenges reinforce the use of TCM, despite policy changes advocating for student-centered methods. (LCM). This study recommends enhancing teacher training programs that focus on fostering student engagement and addressing student ability perceptions to align teaching practices with modern educational goals.